2012
DOI: 10.7193/dm.067.37.48
|View full text |Cite
|
Sign up to set email alerts
|

Consommer des produits alimentaires locaux - Comment et pourquoi ?

Abstract: Version finale à paraître dans Décisions Marketing, 2012, juillet-septembre, n°67. 1 Cette recherche est financée dans le cadre du programme de recherche PSDR-Liproco sur les « démarches de valorisation des produits alimentaires et activités connexes fondées sur les proximités producteurs-consommateurs ». Nous remercions Anne-Hélène Prigent-Simonin pour son implication dans une version préliminaire de l'article ainsi que tous les participants au projet, acteurs et chercheurs, pour les informations fournies, à … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
26

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 12 publications
0
19
0
26
Order By: Relevance
“…The influence of geographical origin has been addressed in terms of the country or region (Van Ittersum et al, 2003; Verlegh and Steenkamp, 1999). Various qualitative studies have revealed the associated representations and motivations to buy local food (Merle and Piotrowski, 2012; Roininen et al, 2006; Seyfang, 2006). These studies, however, focus on specific targets: (1) purchasers through direct sales – not allowing the effect of local origin to be distinguished from the effect of the distribution channel and (2) purchasers of organic products – not allowing the effect of local origin to be distinguished from that related to the production method.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…The influence of geographical origin has been addressed in terms of the country or region (Van Ittersum et al, 2003; Verlegh and Steenkamp, 1999). Various qualitative studies have revealed the associated representations and motivations to buy local food (Merle and Piotrowski, 2012; Roininen et al, 2006; Seyfang, 2006). These studies, however, focus on specific targets: (1) purchasers through direct sales – not allowing the effect of local origin to be distinguished from the effect of the distribution channel and (2) purchasers of organic products – not allowing the effect of local origin to be distinguished from that related to the production method.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…The same applies to indication of local origin. Qualitative studies showed that some consumers associate local agriculture with production models opposed to intensive agriculture, thereby ensuring the health quality of the product (Merle and Piotrowski, 2012; Roininen et al, 2006). Reducing the perceived distance between the producer and the consumer could re-establish the link between local produce and nature, a link that may be reassuring and an indicator of quality (Gallen, 2005; Poulain, 2002).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…41-42), « la circumnavigation propre à Internet serait en train de créer de nouvelles manières d'être, de changer en profondeur la structure du lien social ». On assisterait à l'avènement de la « consocratie », véritable démocratisation de l'innovation et de la production 7 (Von Hippel, 2005) et de l'achat, dont la forme avancée est le consumerto-consumer et les formes alternatives de commerce comme les AMAP, les ventes directes de producteurs, le troc de services, le tout médiatisé par les réseaux sociaux électroniques (Merle et Piotrowski, 2012). Cette « consocratie » serait l'expression commerciale de la « société du Powershift » prophétisée par Toffler (1990) et Agamben (1990) où les citoyens/ consommateurs seraient devenus des « singularités quelconques » renfermant des frustrations à l'égard des formes instituées de la sphère politique, sociale et marchande et revendiqueraient une sorte d'autogestion de leur rapport à la société, notamment à travers Internet (Cova et Carrère, 2002 ;Badot et Cova, 2003).…”
Section: Vers Une « Consocratie Liquide » ?unclassified